The Effect of Silence on the Human Communication System - Utulu, Anthony U.; Bello, David (European Scientific Journal, ESJ, 2023)
Every communication encounter primarily starts because initiators aim to inform and influence others. Silence is a form of nonverbal communication that can be deployed by those communicating. Since nonverbal communication complements the verbal form of communication, it is expected that it is effectively used to enhance the sender-receiver’s communication gains. This paper investigated if leaders’ silence affects public perception, interpretation, and the meaning assignment to a communicated message, using the former Nigerian President, Muhammadu Buhari, and the Nigerian public as cases. It adopted a qualitative approach-an in-depth interview method, using an interview guide as the instrument for data collection. The data analyzed showed that adopting silence as a form of communication, especially during a crisis, harms the human communication experience. Buhari’s silence toward Fulani herders’ attacks affected how the masses perceived, interpreted, and assigned meaning to his action. It allowed conspiracy theories to thrive as public opinion showed that his silence encouraged the herders’ nefarious actions.